PELATIHAN FITUR TRACK CHANGES PADA MICROSOFT WORD UNTUK MAHASISWA JURUSAN PETERNAKAN DI POLBANGTAN YOGYAKARTA-MAGELANG - Adi Fathul Qohar; Mugiarto Mugiarto; Ujud Supriaji; Vian Dwi Chalisty; Panji Prasetyo; Nunur Nuraeni; Efrilia Tri Wahyu Utami; Fitri Rahmawati (Pusat Riset dan Inovasi Nasional, 2022)
Microsoft word is a word processing software in document creation that is the mainstay of Microsoft. In this software there is a track changes feature which functions to track changes made by the reviewer in carrying out the review work. The purpose of the training is to train students in using the track changes feature in Microsoft Word. The training conducted at the Polbangtan Yogyakarta-Magelang hall is a form of community service, especially students. The stages of service are 1. socialization of the track changes feature in Microsoft word; 2. carry out training on these features by students; 3. evaluation of training programs. The result of community service is that post-training Polbangtan livestock department students are able to apply the track changes feature in Microsoft word software.